Valutare la ricerca sociale: problemi e definizioni - Alberto Baldissera (Quaderni di Sociologia, 2017)
For over 15 years an assessment of scientific research has taken place in Italy. The assessment is organized and directed by government agencies such as Anvur (National Agency for Evaluation of the University System and Research). Their activities have met many criticisms, even radically opposed to the assessment, coming first of all from the humanities and the social sciences. La valutazione possibile of Andrea Bonaccorsi, an academic who has been part of Anvur, aims to respond to criticism and to defend the public evaluation of research. The book’s targets are above all the criticisms of P. Bourdieu and of the postmodern tradition. Much of them insist on the incompatibility between quantity and quality. From this point of view it is not possible to transform judgments into numbers. The book contains arguments that can be shared. However, more clarity and precision would be required. This applies to the theories of concepts, of measurement, of indicators and of comparison. Moreover, in order to empirically control their hypotheses, social sciences must reach an agreement on the meaning of the terms used. A requirement often overlooked. Here the public evaluation of the research could effectively stimulate greater agreement among social scientists.